Providing transport for social inclusion within a framework for environmental justice in the UK - Lucas, K (Elsevier, 2006)
This paper examines emerging trends in transport policy in the UK, as identified by the 2004 Transport White Paper and the supporting policy guidance to local transport authorities for addressing social exclusion through local transport provision; accessibility planning. It moves on to identify potential barriers to delivery at the local level and more fundamental challenges, risk and policy tensions. In this context, it critiques UK policies to deliver social equity through transport programmes in light of its Climate Change Agenda and the identified need to significantly reduce traffic levels on UK roads. It identifies the potential synergy between these two policy ambitions, but argues that currently there is a serious policy conflict between these agendas within the UK policy framework. In the light of this conclusion, it offers some key recommendations on the best way forward, which it recommends must be based on the synergistic and integrated delivery of policies for social and environmental equity within the transport sector. It concludes by identifying the key challenges this implies for applied research in this area.